LncRNA POU3F3 Promotes Cancer Cell Proliferation, Migration, and Invasion in Renal Cell Carcinoma by Downregulating LncRNA GAS5 - Lei Zhang; Cezheng Wang; Min Ma (Karger Publishers, 2021)
Background: LncRNAs play regulatory roles in diverse nephrological disorders, including renal cancer. Overexpression of lncRNA POU3F3 (POU3F3) has only been reported in esophageal squamous-cell carcinomas, indicating POU3F3 may be an oncogene in this disease. LncRNA GAS5 (GAS5) was reported to be a suppressor in various tumors. However, the roles and underlying mechanism of POU3F3 and GAS5 involved in renal cell carcinoma (RCC) remain unknown. Methods: Real-time quantitative PCR and in situ hybridization were performed to determine the expression of POU3F3 and GAS5 in paired tumor and adjacent healthy tissues donated by 68 RCC patients. The prognostic values of POU3F3 and GAS5 for RCC were analyzed by performing a 5-year follow-up study. Overexpression of POU3F3 and GAS5 was achieved in RCC cells to explore the interactions between them. Transwell assay and cell proliferation assay were performed to evaluate the role of POU3F3 and GAS5 in regulating RCC cell proliferation, migration, and invasion. Results: In the present study, we found that POU3F3 was upregulated while GAS5 was downregulated in tumor tissues than that in adjacent healthy tissues of patients with RCC. In situ hybridization analysis showed that POU3F3 was mostly expressed in tumor tissues, while GAS5 was mostly expressed in adjacent healthy tissues. High level of POU3F3 and low level of GAS5 were closely correlated with poor prognosis of RCC patients. Expression levels of POU3F3 and GAS5 were significantly and inversely correlated in tumor tissues but not in adjacent healthy tissues of RCC patients. Overexpression of POU3F3 mediated the downregulation of GAS5 in RCC cells, while GAS5 overexpression failed to significantly affect POU3F3 expression. Overexpression of POU3F3 led to promoted, while GAS5 overexpression led to inhibited proliferation, migration, and invasion of RCC cells. In addition, GAS5 overexpression attenuated the enhancing effects of POU3F3 overexpression on cancer cell proliferation, migration, and invasion. Conclusion: POU3F3 promoted cell proliferation, migration, and invasion in RCC possibly by downregulating GAS5.